THE PRINCIPLE OF VOLUNTARY PARTICIPATION OF CITIZENS OF THE RUSSIAN FEDERATION IN ELECTIONS: FOR AND AGAINST - Adygezalova, Gyulnaz; Kovtun, Olga; Tereshchenko, Natalia; Dzidzoev, Ruslan; Shapiro, Irina (Revista Inclusiones, 2020)
The purpose of this work is to study the principle of voluntary participation of citizens of the Russian Federation in elections. General scientific methods were used in the course of the study, among which historical, comparative, and logical. Sociological methods contributed to the collection of information: the method of analyzing legal documents, which allowed concluding the legal consolidation of the principle of voluntary participation of citizens in elections in the conditions of building a legal state and securing the constitutional rights and freedoms of citizens; as well as the observation method, which, using statistical data, helped to identify the attitude of Russian citizens to forced voting. In modern conditions of improving democratic institutions and developing the political system of Russian society, the process of forming political and legal consciousness of citizens and their attitude to the expediency of participating in election campaigns continues. Having studied the theoretical and legal aspects of the right of citizens to participate in the management of state affairs, the authors note the constitutional significance of the principle of voluntary participation in elections.